Emergency Psychiatric Consultations During and After the COVID-19 Lockdown in Italy. A Multicentre Study - Balestrieri, Matteo; Rucci, Paola; Amendola, Davide; Bonizzoni, Miki; Cerveri, Giancarlo; Colli, Chiara; Dragogna, Filippo; Ducci, Giuseppe; Elmo, Maria Giuseppa; Ghio, Lucio; Grasso, Federico; Locatelli, Clara; et al. (Frontiers in Psychiatry, 2021)
Aims The aim was to analyse the psychiatric consultations in nine Italian hospital emergency departments, by comparing the lockdown and post-lockdown periods of 2020 with the equivalent periods of 2019. Methods Characteristics of psychiatric consultations, patients, and drug prescriptions were analysed. Joinpoint models were used to identify changes in the weekly trend of consultations. Results A 37.5% decrease in the number of consultations was seen during the lockdown period and 17.9% after the lockdown. The number of patients decreased by 34.9% during the lockdown and 11.2% after the lockdown. A significant change in the number of consultations from week 11 to week 18 occurred, followed by a gradual increase. There was a higher percentage of patients with previous psychiatric hospitalizations during the lockdown period (61.1% vs 56.3%) and a lower percentage after the lockdown (59.7% vs 64.7%). During the lockdown there was a large increase of substance use disorders, whereas more manic episodes occurred after the lockdown. A 3.4% decrease was observed in suicidal ideation and planning during the lockdown, followed by an upward rebound after the lockdown, along with an increase in suicide attempts. During lockdown antipsychotic and benzodiazepine prescriptions increased by 5.2% and 4.1%, respectively. After the lockdown, the number of compulsory hospitalizations was higher than in 2019. Conclusions We observed a decrease of psychiatric consultations during and after the lockdown. There was an increase in consultations for manic episodes and suicidality after the lockdown. The focus of psychiatric services must remain high particularly in this latter period.